2020
DOI: 10.20524/aog.2020.0560
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of symptomatic uncomplicated diverticular disease: a long-term follow-up study

Abstract: Background Symptomatic uncomplicated diverticular disease (SUDD) affects about 20% of patients who have diverticulosis. However, the natural history of SUDD is not yet completely understood. Our aim was to assess the outcomes of a cohort of SUDD patients during a long-term follow up. Methods One hundred eighty-five patients suffering from SUDD were identified from a large electronic database. Symptoms assessed were abdominal pain, bloating, bowel movement/day, each of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“… 19 Moreover, Tursi et al reported that among 185 patients with SUDD, acute diverticulitis occurred in 7.6% and surgery was required in 3.2% after a median follow-up time of 13 years. 10 The difference in acute diverticulitis rate between the studies is consistent with the more rigorous inclusion criteria to define SUDD used by Tursi et al and with different follow-up periods. Importantly, all three studies demonstrated that SUDD is a chronic and distinct clinical entity.…”
Section: Symptomatic Uncomplicated Diverticular Diseasesupporting
confidence: 76%
See 2 more Smart Citations
“… 19 Moreover, Tursi et al reported that among 185 patients with SUDD, acute diverticulitis occurred in 7.6% and surgery was required in 3.2% after a median follow-up time of 13 years. 10 The difference in acute diverticulitis rate between the studies is consistent with the more rigorous inclusion criteria to define SUDD used by Tursi et al and with different follow-up periods. Importantly, all three studies demonstrated that SUDD is a chronic and distinct clinical entity.…”
Section: Symptomatic Uncomplicated Diverticular Diseasesupporting
confidence: 76%
“…SUDD’s natural history has been explored by three studies with a follow-up period of at least 5 years after diagnosis. 10 , 18 , 19 As reported by Salem et al, among 163 patients with SUDD, acute diverticulitis occurred in 1.7%, and surgery was required in 0.9% after a mean follow-up time of 5 years. 18 While the REMAD Registry reports among 300 patients with SUDD, a 1.6% incidence of acute diverticulitis after only 1 year of follow-up.…”
Section: Symptomatic Uncomplicated Diverticular Diseasementioning
confidence: 83%
See 1 more Smart Citation
“…Only a minority will develop acute diverticulitis (AD), characterized by acute inflammation of the diverticula [ 1 ]. Although the prevalence of SUDD and AD are lower than expected [ 2 , 3 , 4 ], we do not yet know why some patients with diverticulosis develop symptoms while others do not. There are data in the recent literature pointing out the possible role of gut microbiota (GM) as a critical factor in the pathogenesis of several gastrointestinal (GI) and extraintestinal (EI) diseases, improving the understanding of the highly complex interaction between GM and innate and adaptive immunity in regulating inflammation [ 5 ].…”
Section: Introductionmentioning
confidence: 81%
“…Rifaximin has been used to treat Symptomatic Uncomplicated Diverticular Disease in a clinical trial and results were encouraging, in terms of symptom control. Interestingly, the changes in clinical presentation, also corresponded to changes in faecal microbiota composition, with a reduction of Roseburia, Veillonella, Streptococcus and Haemophilus [ 69 ]. In another study, also Akkermansia resulted reduced [ 70 ].…”
Section: Microbiota and Acute Diverticulitismentioning
confidence: 99%